2021
DOI: 10.3390/molecules26175399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin II on Erythropoietin Production in the Kidney and Liver

Abstract: The kidney is a main site of erythropoietin production in the body. We developed a new method for the detection of Epo protein by deglycosylation-coupled Western blotting. Detection of deglycosylated Epo enables the examination of small changes in Epo production. Using this method, we investigated the effects of angiotensin II (ATII) on Epo production in the kidney. ATII stimulated the plasma Epo concentration; Epo, HIF2α, and PHD2 mRNA expression in nephron segments in the renal cortex and outer medulla; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…In previous studies, we showed that Epo production is regulated not only by hypoxia but also by the renin-angiotensin-aldosterone system [ 35 , 37 , 38 ]. We previously showed that fludrocortisone and angiotensin II stimulated Epo production by the nephron, especially in the intercalated cells of the collecting duct [ 35 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we showed that Epo production is regulated not only by hypoxia but also by the renin-angiotensin-aldosterone system [ 35 , 37 , 38 ]. We previously showed that fludrocortisone and angiotensin II stimulated Epo production by the nephron, especially in the intercalated cells of the collecting duct [ 35 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney sections were immuno-stained as described previously [ 35 , 37 , 38 , 47 ]. In brief, the sections were blocked with 5% normal goat serum and reacted with rabbit polyclonal anti-human Epo antibody (sc-7956, 1:10; Santa Cruz Biotechnology, Santa Cruz, CA, USA), followed by Histofine Simple Stain MAX-PO (414341F; Nichirei Bioscience, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, hyperlipidemia can lead to renin-angiotensin-aldosterone system activation and high levels of angiotensin II, which further leads to increased renal erythropoietin secretion and reticulocyte count. 39 Likewise, studies on the association between reticulocyte count and BP are also rare. Only one study reported that reticulocyte levels were positively associated with hypertension in elderly Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2-mediated downregulation of ACE2, removes the protective arm of the RAAS and increases angiotensin II (Ang II) and aldosterone [ 1 ]. Elevated Ang II and aldosterone are both master regulators of erythropoietin (EPO) homeostasis and engage host humoral and tissue RAAS to induce EPO oversecretion that we posit is protective against SARS-CoV-2 infection in children and young adults [ [2] , [3] , [4] ]. Due to lower ACE2 expression in children, this SARS-CoV-2-mediated ACE/ACE2 imbalance, swiftly and potently calls upon an innate immune response motif with EPO as the main protagonist mediating a phylogenetically preserved, tissue protective mechanism mitigating tissue injury and pathogen invasion at an early age [ 2 ].…”
mentioning
confidence: 99%